2021
DOI: 10.21203/rs.3.rs-322306/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interactions between Caveolin 1 polymorphism and the Mediterranean and Mediterranean-DASH Intervention for Neurodegenerative Delay diet (MIND) diet on Metabolic dyslipidemia in overweight and obese adult women: a cross-sectional study

Abstract: Objective: A higher incidence of metabolic dyslipidemia (MD) and its association with many diseases attracted considerable attention to its control. Caveolin 1 (CAV1) is a known gene associated with obesity. Today, a novel diet recognized as the Mediterranean and Mediterranean-DASH Intervention for Neurodegenerative Delay diet (MIND( is reported to have a positive effect on overall health. Hence, we aimed to investigate the interactions between CAV1 polymorphism and MIND diet on the MD in overweight and obese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Previous studies showed that the MC4R variant has an association with higher BMI and WC in children and adults [55,56]. A-allele carriers of the CAV-1, which is abundant in adipocytes [25], had a significantly higher BMI [29,30]. Also, Cry − 1 has an important role in metabolism [31] and the C-allele of the Cry-1 polymorphism can lead to significantly higher obesity indices such as BMI, weight, WC, and hip circumferences [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that the MC4R variant has an association with higher BMI and WC in children and adults [55,56]. A-allele carriers of the CAV-1, which is abundant in adipocytes [25], had a significantly higher BMI [29,30]. Also, Cry − 1 has an important role in metabolism [31] and the C-allele of the Cry-1 polymorphism can lead to significantly higher obesity indices such as BMI, weight, WC, and hip circumferences [34].…”
Section: Discussionmentioning
confidence: 99%
“…Over the preceding decade, a large variety of studies have implicated CAV-1 SNP in the development of hypertension, dyslipidemia, and atherosclerosis [26][27][28]. It is worth noting that A-allele carriers of the CAV-1 rs3807992 had significantly higher BMI [29,30]. Cryptochromes (Cry) 1, the principal component of the negative limb of the core clock, appears to play important roles in metabolism [31] such as regulating glucose homeostasis [32].…”
Section: Introductionmentioning
confidence: 99%